Experimental investigation on end milling of GFRP by using Taguchi optimization. (2023) - Jasper, S.; Ravichandran, M.; Vijayakumar, D.
Abstract: This research work is focused on the Glass fibre reinforced plastics (GFRP) through the help of the end milling technique on different fibre orientation with various input and output process parameter. Material removal rate (MRR), Surface roughness (Ra), Machining Time (MT) has been analyzed. The investigational results were carried out under the L27 orthogonal array through the design of experiments. The analysis of Means (ANOM) and the analysis of Variance (ANOVA) used determine the optimal levels of the input parameters and also it can be able to identify the level of Surface Roughness (Ra), Machining Time (MT), Material removal rate (MRR). As a result, process parameters make a significant contribution, for material removal rate, depth of cut (Doc) plays a vital role. For material removal rate the optimal control factor is (speed – 1500 rpm), (Feed – 0.06 mm/rev) (Doc −1.3 mm)For Machining Time the optimal control factor is (speed – 1000 rpm), (Feed – 0.08 mm/rev) (Doc −1.3 mm)For surface roughness the optimal control factor is (speed – 2000 rpm), (Feed – 0.04 mm/rev) (Doc −1.1 mm)